Fundamental of Entrepreneurship ENT300 : Wardah Boutique / Farahafiza Basheer Ahmed ... [et al.] - Basheer Ahmed, Farahafiza; Abdul Rahman, Norfazleena; Kamis, Azzrin; Ramden, Nur Ainon (2014)
Our business is fully own by partnership. A partnership is a legal business entity with two or more partner. It easier to secure financial assistance from financial institutions compared with sole partnerships. A lot of ideas, talents and skills can be pooled together for better management of our business. We will provide many various types of hijab’s from a various types of materials which meets the satisfied of our customer and also concern about providing the best services.